IMPLEMENTASI METODE FUZZY MAMDANI PADA APLIKASI INVENTORY UNTUK PREDIKSI PENGADAAN BARANG DI PT.PERTAMINA (PERSERO) PERKAPALAN - Redaksi Tim Jurnal (PETIR, 2017)
In ship operations required the most recent technology infrastructure. Infrastructure needs such as supporting system in office and ship. This is provided by the function of IT (Information Technology) Shipping. Therefore, to meet all the needs in the office and ship, the IT Shipping function should always provide sufficient stock of goods. One method that can be used for the procurement of an item that is using fuzzy mamdani logic method. So that IT Shipping function can know the estimated goods that will be provided for the needs at the office or on board. Variables used amounted to 3 variables that are 2 input variables and 1 variable output. Of the 3 variables consists of 3 fuzzy set that is low, normal, high. The results of the study stated that the inventory prediction application of goods procurement can help employees know the number of procurement of goods to be provided next.